The relationship between clean and healthy lifestyle behavior (phbs) with diarrhea incidence in Toddlers at Mekar Baru Health Center year 2022 - Saidah, Dede (Vanchapo Health Science Journal, 2023)
Background.According to data from the World Health Organization (WHO) in 2012, there are more than one billion cases of gastroenteritis every year. The morbidity rate for diarrhea in 2011 was 411 sufferers per 1000 population. It is estimated that 82% of deaths from rotavirus gastroenteritis occur in developing countries, especially in Asia and Africa, where access to health and nutritional status is still a problem.Research purposes.The general objective is to find out the relationship between clean and healthy living behavior (PHBS) and the incidence of diarrhea in toddlers at the Mekar Baru Health Center in 2022.Method.This study uses two variables, namely the independent variable and the dependent variable. The independent (independent) variable is a variable that influences or becomes the cause of the change or the emergence of the dependent variable, while the dependent (bound) variable is a variable that is affected or due, because of the independent variableResults.There is a significant correlation between the incidence of diarrhea and clean water, healthy latrines, and weighing the baby (marked with ), with a p-value of less than 0.05. This shows that there is a significant relationship between these variables. However, the relationship between the incidence of diarrhea and exclusiveness is not significant (p-value > 0.05), so it cannot be said that there is a strong relationship between the two variables.Conclusion.Overall, it is important to increase public knowledge, awareness and understanding of the implementation of PHBS which includes hand washing, use of clean water, healthy latrines and exclusive breastfeeding. Education programs, campaigns and support from health workers can help reduce the risk of diarrhea and improve overall community health at the UPTD Puskesmas Mekar.